Koeksistensi Damai dalam Masyarakat Muslim Modernis - Hendar Riyadi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
This study argues that puritan Islam is not always being a threat to pluralism. This is evidenced by modern Muslims (Muhammadiyah) in Arjasari of Bandung District, whose views and attitudes tend towards a peaceful coexistence. They have positive view of diversity of religions; they empasize charity dialogue (not violance) in competing with Christian missionary activities; and their social behavior and acts show tolerance and peaceful coexistence with non-Muslim family. These experiences are correcting the claim of some scholars that puritan Islam can hardly accept religious diversity and even viewed as threat to pluralism. Using qualitative methods, this study concludes that the Muhammadiyah Muslim community of Arjasari shows a positive view of pluralism and peaceful coexistence attitude towards non-Muslims, and, hence, that puritan Islam is not a threat to pluralism.